High dose caffeine citrate for extubation of preterm infants: a randomised controlled trial. Issue 6 (21st October 2004) - Steer, P; Flenady, V; Shearman, A; Charles, B; Gray, P H; Henderson-Smart, D; Bury, G; Fraser, S; Hegarty, J; Rogers, Y; Reid, S; Horton, L; et al.
Abstract : Objective: To compare two dosing regimens for caffeine citrate in the periextubation period for neonates born at less than 30 weeks gestation in terms of successful extubation and adverse effects. Design: A multicentre, randomised, double blind, clinical trial. Setting: Four tertiary neonatal units within Australia. Patients: Infants born less than 30 weeks gestation ventilated for more than 48 hours. Interventions: Two dosing regimens of caffeine citrate (20 v 5 mg/kg/day) for periextubation management. Treatment started 24 hours before a planned extubation or within six hours of an unplanned extubation. Main outcome measure: Failure to extubate within 48 hours of caffeine loading or reintubation and ventilation or doxapram within seven days of caffeine loading. Results: A total of 234 neonates were enrolled. A significant reduction in failure to extubate was shown for the 20 mg/kg/day dosing group (15.0% v 29.8%; relative risk 0.51; 95% confidence interval (CI) 0.31 to 0.85; number needed to treat 7 (95% CI 4 to 24)). A significant difference in duration of mechanical ventilation was shown for infants of less than 28 weeks gestation receiving the high dose of caffeine (mean (SD) days 14.4 (11.1) v 22.1 (17.1); p  =  0.01). No difference in adverse effects was detected in terms of mortality, major neonatal morbidity, death, or severe disability or general quotient at 12 months. Conclusions: This trial shows short term benefits for a 20 mg/kg/day dosing regimen of caffeine citrate for neonates born at less than 30 weeks gestation in the periextubation period, without evidence of harm in the first year of life.